Cultural Strategy of Saving Money Madura's Kelontong Shop In Business Income - R. Suhaimi; Nasrullah Nasrullah; Abdul Hamid Bhustomi Nur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
elontong (traditional grocery) stores represents a unique and intriguing socio-economic phenomenon. This informal financial habit, rooted in community tradition, is widely observed across Madurese grocery store owners in various regions, including Malang. However, this cultural practice has received limited academic attention, particularly in terms of its functions, motivations, and implications. The objective of this study is to explore the cultural practice of saving money among Madurese-owned grocery stores in Malang, focusing on its underlying purpose, mechanism, and socio-economic significance. This research uses a descriptive qualitative approach, with data collected through in-depth interviews and direct observation of selected Madurese store owners operating in urban and suburban Malang. The findings reveal that this saving culture follows a consistent pattern—where 10% of daily sales are set aside every 24 hours. This practice is not formally recorded or banked but is stored securely within the shop environment or in a trusted informal setting. The saved income is intended not only for profit accumulation but also for strategic financial readiness, such as for restocking inventory, covering emergency expenses, or fulfilling family and social obligations. The study concludes that this saving behavior is both an economic and cultural strategy, serving as a grassroots financial management model embedded in local values of discipline, foresight, and community solidarity. The findings contribute to the field of cultural economics and micro-enterprise finance by highlighting how traditional practices can serve as sustainable informal financial systems among ethnic business communities.